2021
DOI: 10.3168/jds.2021-20411
|View full text |Cite
|
Sign up to set email alerts
|

Disbudding and dehorning practices for preweaned dairy calves by farmers in Wisconsin, USA

Abstract: Many dairy farmers in North America disbud or dehorn their cattle to improve human and animal safety. The Farmers Assuring Responsible Management (FARM v. 4.0) program requires that disbudding be performed before 8 wk of age with pain-control medication. The objective of this observational cross-sectional study was to quantify disbudding and dehorning practices of Wisconsin dairy producers to target future extension programming. Responses from 217 Wisconsin dairy producers and calf raisers were collected via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…According to our unpublished data, more than 90% of the dairy farms in China use caustic paste as their primary disbudding method. This proportion is dramatically higher than that in the UK [ 17 ], Europe [ 18 ], and North America [ 19 ]. It should be noted that most studies and recommendations suggest hot iron as a preferable method for disbudding since it induces less total plasma cortisol responses [ 20 ] and less negative impact on calves’ behaviours [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our unpublished data, more than 90% of the dairy farms in China use caustic paste as their primary disbudding method. This proportion is dramatically higher than that in the UK [ 17 ], Europe [ 18 ], and North America [ 19 ]. It should be noted that most studies and recommendations suggest hot iron as a preferable method for disbudding since it induces less total plasma cortisol responses [ 20 ] and less negative impact on calves’ behaviours [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…One difference worth identifying is that some of these studies demonstrate a greater use of pain mitigation for dehorning or disbudding as compared with those reported for castration. Saraceni et al ( 33 ) reported that 43% of Wisconsin producers provided pain control medication to calves for disbudding; the study was conducted prior to the disbudding requirements in FARM 4.0 ( 31 ). Hewson et al ( 18 ) reported a greater percentage of calves receiving pain mitigation (76% dairy, 54% beef) for dehorning than for castration.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the FARM (Farmers Assuring Responsible Management) Animal Care program Version 4.0 requires the use of pain mitigation for disbudding ( 31 ) but defers to veterinarian recommendation for pain control associated with castration and branding. Although more recent veterinarian and producer surveys have shown an increase in reported pain mitigation use for common husbandry procedures ( 32 , 33 ), most studies have not demonstrated full integration of pain mitigation into best management procedures for cattle.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 survey of Canadian producers reported that 86% of respondents used cautery disbudding as their primary method and 9% used caustic paste (Winder et al, 2018a). Similarly, in the United States in 2014, 70% of respondents reported disbudding their calves with a cautery iron and 16% with caustic paste (NAHMS, 2018); however, there may be regional differences in the use of disbudding products, as a recent survey performed among Wisconsin producers reported that 61% of respondents use of caustic paste for disbudding (Saraceni et al, 2021). Animals above 3 mo of age typically require surgical amputation dehorning.…”
Section: Disbudding Methodsmentioning
confidence: 99%